THE LECTURER-STUDENT CONVERSATIONAL STRUCTURE IN PRAGMATICS LEARNING INTERACTION - Diah Widya Ningrum; Didik Santoso (Universitas Islam Sumatera Utara (UISU), 2021)
This study aims to describe the structure of the lecturer-student conversation in the interaction of Pragmatics Class. This type of research is descriptive qualitative. The technique of data collection is done by recording and note-taking techniques. The data analysis technique is carried out by heuristic techniques. The results of the study show that the interaction of the lecturer and the students in Pragmatics Class have conversational structures: 1) turn taking of speech that occurs because of the opportunity to speak, 2) pauses (long and short) that occur due to the absence of feedback in the form of speech and speakers feel hesitant in conveying the message. 3) Overlaps that occur due to speech or the use of the same lingual element, 4) backchannels that occur because there is understanding and acceptance or approval of the speech, and 5) adjunct pairs that occur because of greetings, questions, and requests. This indicates that the process of the lecturer-students interaction runs well. The students feel enthusiastic for responding the lecturer’s questions.